2004
DOI: 10.1038/sj.bjp.0705640
|View full text |Cite
|
Sign up to set email alerts
|

Epoxyeicosatrienoic acids mediate adenosine‐induced vasodilation in rat preglomerular microvessels (PGMV) via A2A receptors

Abstract: 1 Activation of rat adenosine 2A receptors (A 2A R) dilates preglomerular microvessels (PGMV), an effect mediated by epoxyeicosatrienoic acids (EETs). 2 Incubation of PGMV with a selective A 2A R agonist, 2-p-(2-carboxyethyl) phenethylamino-5 0 -Nethylcarboxamidoadenosine (CGS 21680; 100 mM), increased isolated PGMV EET levels to 7.5771.53 ng mg À1 protein from 1.0670.22 ng mg À1 protein in controls (Po0.05), without affecting hydroxyeicosatetraenoic acid (HETE) levels (10.870.69 vs 11.0270.74 ng mg À1 protein… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

14
59
0

Year Published

2004
2004
2015
2015

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(73 citation statements)
references
References 46 publications
14
59
0
Order By: Relevance
“…18,47 EETs have been reported to exhibit diverse biologic activities, including dilation of preglomerular microvessels, 48 stimulation of angiogenesis, 49 and inhibition of sodium transport. 20 It is reported that 8,9-and 14,15-EET could also regulate BK channels 23,24 ; however, the observation that only 11,12-EET stimulates BK channels strongly suggests that 11,12-EET mediates the effect of AA on BK channels in the CCD.…”
Section: Discussionmentioning
confidence: 99%
“…18,47 EETs have been reported to exhibit diverse biologic activities, including dilation of preglomerular microvessels, 48 stimulation of angiogenesis, 49 and inhibition of sodium transport. 20 It is reported that 8,9-and 14,15-EET could also regulate BK channels 23,24 ; however, the observation that only 11,12-EET stimulates BK channels strongly suggests that 11,12-EET mediates the effect of AA on BK channels in the CCD.…”
Section: Discussionmentioning
confidence: 99%
“…Stimulation of A 1 receptor has been shown to cause inhibition of adenylate cyclase, decrease in cAMP concentrations, activation of PKC, and stimulation of phospholapase A 2 (PLA2) (26), whereas stimulation of A 2a or A 2b receptor has been reported to increase cAMP production and stimulate PKA (26). Recently, it has also been reported that stimulation of A 2a receptor increases 11,12-and 5,6-EET in the kidney (6). The RT-PCR analysis has detected A 1 and A 2b adenosine receptor mRNAs, whereas the band intensity for A 2a adenosine receptor mRNA is low in the TAL (28,33).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, it has been shown that EET activates Gs protein and Src family PTK (25). For instance, 11,12-EET has been reported to enhance PKA activity by increasing cAMP formation in the smooth muscle of renal vessels (6). Also, 14,15-EET has been demonstrated to activate PTK-dependent signaling (5).…”
Section: Discussionmentioning
confidence: 99%
“…A 2 receptor-mediated vasodilation results from stimulation of G s , leading to increased cAMP that is partially mediated via epoxyeicosatrienoic acid (EETs) release (7). Cytochrome P-450 epoxygenase metabolites alter vascular tone in afferent arterioles and modify the autoregulatory efficiency of the preglomerular microcirculation (8,20). Activation of A 2 receptor stimulates EETs in preglomerular microvessels, suggesting that it may affect the following major indexes of renal function: renal vascular resistance, glomerular filtration rate, renal interstitial pressure, and medullary blood flow (8).…”
mentioning
confidence: 99%
“…Cytochrome P-450 epoxygenase metabolites alter vascular tone in afferent arterioles and modify the autoregulatory efficiency of the preglomerular microcirculation (8,20). Activation of A 2 receptor stimulates EETs in preglomerular microvessels, suggesting that it may affect the following major indexes of renal function: renal vascular resistance, glomerular filtration rate, renal interstitial pressure, and medullary blood flow (8). Adenosine also dilates efferent arterioles at concentrations compatible with activation of the A 2B receptor subtype (1).…”
mentioning
confidence: 99%